Internal Carotid Injury during Skull Base Surgery-Case Report and a Review of the Literature - Matoušek, Petr; Krejčí, Tomáš; Misiorzová, Eva; Lipina, Radim; Procházka, Václav; Lubojacký, Jakub; Čábalová, Lenka; Komínek, Pavel (Brain sciences, 2022)
Iatrogenic injury of the internal carotid artery (ICA) is a rare, and probably underreported, complication of transnasal endoscopic skull base surgery. Although treatment algorithms have been suggested, there is no definite consensus or guideline for the management of this severe complication. We describe a case of ICA injury that occurred during a transsphenoidal biopsy of a tumor in the cavernous sinus and we present a treatment algorithm for managing this complication. We reviewed the articles published from 1998 to 2021, reporting on major vascular injury during transnasal endoscopic skull base surgery and endonasal endoscopic surgery, and we compare the methods and results of ICA injury management reported in the literature with the presented case. The most promising treatment for ICA injury might be packing with a muscle graft initially, then performing an endovascular intervention.
Keywords: transnasal skull base surgery; internal carotid artery injury; angiography; iatrogenic injury; endovascular treatment